Resting State Functional Connectivity Biomarkers of Treatment Response in Mood Disorders: A Review - Taylor, Joseph J.; Kurt, Hatice Guncu; Anand, Amit (Frontiers in Psychiatry, 2021)
There are currently no validated treatment biomarkers in psychiatry. Resting State Functional Connectivity (RSFC) is a popular method for investigating the neural correlates of mood disorders, but the breadth of the field makes it difficult to assess progress toward treatment response biomarkers. In this descriptive review, we followed general PRISMA guidelines to evaluate the evidence base for mood disorder treatment biomarkers across diagnoses, brain network models, and treatment modalities. We hypothesized that no treatment biomarker would be validated across these domains or with independent datasets. Results are organized, interpreted, and discussed in the context of four popular analytic techniques: 1) reference region (seed-based) analysis, 2) independent component analysis, 3) graph theory analysis, and 4) other methods. Cortico-limbic connectivity is implicated across studies, but there is no single biomarker that spans analyses or that has been replicated in multiple independent datasets. We discuss RSFC limitations and future directions in biomarker development.